Wednesday

July 23, 2014

July 23, 2014

Posted by **kingsley** on Wednesday, October 5, 2011 at 6:15am.

- maths -
**Reiny**, Wednesday, October 5, 2011 at 8:39amt(5) = ar^4 = 567

t(3) = ar^2 = 63

divide first equation by the second

ar^4/(ar^2) = 567/63

r^2 = 9

r = ± 3

if r = ±3,

ar^2= 63

a = 7

Since you only want 7 terms, it would probably be faster to just find them and add them up

that is,

7 + 21 + 63 + 189 + 567 + 1701 + 5103 = 7651

or 7 - 21 + 63 - 189 + 567 - 1701 - 5103 = ......

or by formula

if a=7, r= 3

sum(7) = 7(3^7 - 1)/(3-1) = 7651

or if x=-3

sum(7) = 7((-3)^7 - 1)/(-3-1) = .....

**Related Questions**

Maths - The 5th term of an exponential sequence is 4 and of 2nd term is 35(¡)...

Maths - The 3rd term of an AP is 10 more than the first term while the fifth ...

Math - 1) If the sum of the first n terms of a series is Sn where Sn=2n²-n, (a)...

math - 1) If the sum of the first n terms of a series is Sn where Sn=2n²-n, (a)...

arithmetic - An arithmetic n geometric sequence have the same first term 2.with ...

maths - in an A.p 6th term is half the 4th term and the 3rd term is 15.How many ...

Geometric - 1) The sum of last three terms of GP having n terms is 1024 time the...

Math - Name School Team Event 3: Logic and Reasoning (with calculators) 5th/6th ...

maths - There are 6 terms in an A.P. 6th term is 3 times the second term and 4th...

Math - Sum of4th and the 6th terms of an a,p is 42 . While the sum of the 3rd ...